2012
DOI: 10.3109/10826084.2011.631676
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Rights Violations and Perceptions of Discrimination on Health Service Utilization Among Injection Drug Users in Delhi, India

Abstract: The study was conducted from August to December 2007, in two urban, poor neighborhoods in Delhi. A respondent-driven sampling was used to recruit 343 injection drug users who were interviewed with a survey questionnaire that included items of human rights abuses, health service utilization, and sociodemographic characteristics. Multivariate logistic regression with backward selection of variables was conducted with the three outcome variables-service utilization in general care sector, harm reduction, and drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Questions regarding demographics, drug use and sexual behaviours (predominantly condom use with various partners) were adapted from a previous study (Sarin & Kerrigan, 2012) among PWIDs in Delhi and from the Integrated Biological and Behavioural Assessment (IBBA) survey previously undertaken among PWIDs in three states of India (Indian Council of Medical Research & FHI 360, 2011). Recent sexual risk behaviour with female partners was gathered by first asking participants about the number and type of sex partners they had during the preceding six months and then asking whether or not they used a condom at last sex with these partners.…”
Section: Demographics Injecting and Sexual Practicesmentioning
confidence: 99%
“…Questions regarding demographics, drug use and sexual behaviours (predominantly condom use with various partners) were adapted from a previous study (Sarin & Kerrigan, 2012) among PWIDs in Delhi and from the Integrated Biological and Behavioural Assessment (IBBA) survey previously undertaken among PWIDs in three states of India (Indian Council of Medical Research & FHI 360, 2011). Recent sexual risk behaviour with female partners was gathered by first asking participants about the number and type of sex partners they had during the preceding six months and then asking whether or not they used a condom at last sex with these partners.…”
Section: Demographics Injecting and Sexual Practicesmentioning
confidence: 99%
“…33 The latter, however, was to our knowledge the only study to analyse social and structural factors and found that low utilization of healthcare services was associated with exposure to policing, social exclusion and negative healthcare experiences.…”
Section: A Nomentioning
confidence: 99%
“…26 The findings presented herein add to the growing body of evidence that the Thai government's emphasis on aggressive drug law enforcement undermines public health by constraining healthcare access, 19,28 which is consistent with international literature suggesting the negative impact of aggressive policing tactics. 25,33,36,37 As urged by the World Bank and UNAIDS, 4,10,11,38 Thai policymakers should re-examine their ongoing punitive strategies and instead place emphasis on access to comprehensive harm reduction and healthcare services.…”
Section: What This Study Adds?mentioning
confidence: 99%
See 1 more Smart Citation
“…Across India, there are an estimated 2.4 million high-risk MSM (National AIDS Control Organization [NACO], 2006) despite criminalization of homosexuality under the Indian penal code. Poor access to and utilization of HIV services as well as stigma and discrimination are common for both MSM and PWID (Latkin et al, 2010; Mawar, Sahay, Pandit, & Mahajan, 2005; Sarin & Kerrigan, 2012; Thomas et al, 2011). …”
Section: Introductionmentioning
confidence: 99%